Measurement and analysis of fatigue crack deformation on the macro- and micro-scale (Fracture and Structural Integrity, 2015)
The paper describes an experiment which performs in-situ loading of a small compact tensionspecimen in a scanning electron microscope. Images are collected throughout a number of successive loadincgcycles. These are then analysed using digital image correlation (DIC) in order to produce crack flankdisplacements as a function of load. This data is then compared with a simple elastic approach, and it is concludedthat elastic-plastic analysis is required in order to accurately capture the displacements close to the crack tip. Asimple approach due to Pommier and Hamam is therefore employed. This gives a better representation of thedata, but predicts a variation of crack tip displacement, ?, which is difficult to explain from a physical perspective.The need for a more sophisticated analysis of the data is therefore highlighted.
Keywords: Crack Tip Displacements